2006
DOI: 10.1158/0008-5472.can-05-2693
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Identification of Novel Determinants of Response to Chemotherapy in Colon Cancer

Abstract: DNA microarray analysis was used to analyze the transcriptional profile of HCT116 colorectal cancer cells that were treated with 5-fluorouracil (5-FU) or oxaliplatin and selected for resistance to these agents. Bioinformatic analyses identified sets of genes that were constitutively dysregulated in drug-resistant cells and transiently altered following acute exposure of parental cells to drug. We propose that these genes may represent molecular signatures of sensitivity to 5-FU and oxaliplatin. Using real-time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 39 publications
4
90
0
1
Order By: Relevance
“…This study therefore seeks to develop and understand the cytotoxic effect of 56MESS on eukaryotes at gene expression level by the means of transcriptomics. Transcriptomics, a platform which can reveal changes of gene expression at a genome-wide scale, is a powerful holistic approach to profile gene expression for understanding molecular pathways of preclinical and clinical anticancer drugs [7,23,25]. The model eukaryotic organism, yeast Saccharomyces cerevisiae, plays a significant role in this approach [68] due to its easy amendability with various experimental approaches and conservation of genes and essential cellular functions with humans [3].…”
Section: Introductionmentioning
confidence: 99%
“…This study therefore seeks to develop and understand the cytotoxic effect of 56MESS on eukaryotes at gene expression level by the means of transcriptomics. Transcriptomics, a platform which can reveal changes of gene expression at a genome-wide scale, is a powerful holistic approach to profile gene expression for understanding molecular pathways of preclinical and clinical anticancer drugs [7,23,25]. The model eukaryotic organism, yeast Saccharomyces cerevisiae, plays a significant role in this approach [68] due to its easy amendability with various experimental approaches and conservation of genes and essential cellular functions with humans [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although the development and characterization of oxaliplatin-resistant HCT116 colorectal carcinoma cells by repeated exposure to increasing concentrations of oxaliplatin has been reported previously (Boyer et al, 2004(Boyer et al, , 2006, base excision repair protein levels in oxaliplatin-resistant cancer cells have not been characterized. We found that untreated HCT-OR cells had on average 2.2-fold higher levels of Pol b protein than untreated parental HCT116 cells ( Figure 1a, compare lanes 4 and 1, respectively).…”
mentioning
confidence: 99%
“…Our data, while not specifically identifying ERCC1 as a candidate hit, did identify numerous genes involved in the repair of DNA damage, including members of the NER (of which ERCC1 is a key molecule) and DNA MMR pathways (Table 1). It is possible that ERCC1 mRNA levels may predict resistance to oxaliplatin only in the clinical setting of combination therapy with 5-FU (42). In our screen, we treated cells with oxaliplatin alone to reduce the identification of false-positive hits and to simplify the screen design.…”
Section: Resultsmentioning
confidence: 99%